Pakistan: A cost-benefit analysis of crop rotation practice in rainfed areas - Rana, Abdul Wajid; Gill, Sitara; Akram, Iqra (International Food Policy Research Institute, 2024)
Climate change is one of the most pressing challenges confronting our global system today. The scientific community has clearly established that global temperatures are rising and the consequences of climate change may swiftly transition from an environmental risk to an economic threat. Agriculture sector is particularly vulnerable to changes in weather and climatic condition. Over 60% of the yield variability is chalked up to to climate change; significantly affecting food production and farmer income. Changes in climate affect the onset and duration of crop growing cycle, and the extent and duration of heat and water stress impact agriculture production. Moreover, it may trigger pest and disease outbreaks causing significant production losses. Small-scale farmers in rain-fed areas of Pakistan face the severe susceptibility to the challenges brought about by climate change. This vulnerability stems from their heavy dependence on traditional farming methods and their limited ability to adapt, exacerbated by their limited access to advanced technologies and high levels of poverty. Worldwide, crop yields from rainfed farming are approximately 50 percent less than those achieved through irrigated methods. In the absence of adaptation measures to cope with climate change, a potential decline of around 50 percent in rain-fed agricultural yields could potentially occur within the next 30-35 years. Promoting climate smart agricultural practices appears to be a dependable strategy for addressing risks posed by climate change.